2016
DOI: 10.1016/j.cognition.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

I see what you say: Prior knowledge of other’s goals automatically biases the perception of their actions

Abstract: We investigated whether top-down expectations about an actor's intentions affect action perception in a representational momentum (RM) paradigm. Participants heard an actor declare an intention to either take or leave an object and then saw him either reach for or withdraw from it, such that action and intention were either congruent or incongruent. Observers generally misperceived the hand's disappearance point further along the trajectory than it actually was, in line with the idea that action perception inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 31 publications
7
79
0
Order By: Relevance
“…In particular Hudson et al (2016a) have demonstrated that hearing an actor declare his intention to take (or leave) an object before observing him reaching for (or withdrawing from) it, significantly modified the perceptual judgment of his hand position. In this study, however, the meaning of the verbal input played a relevant role, informing the observers of the actor's intention and biasing their perception even further toward the expected goal [see also Hudson et al (2016b)].…”
Section: Discussionmentioning
confidence: 99%
“…In particular Hudson et al (2016a) have demonstrated that hearing an actor declare his intention to take (or leave) an object before observing him reaching for (or withdrawing from) it, significantly modified the perceptual judgment of his hand position. In this study, however, the meaning of the verbal input played a relevant role, informing the observers of the actor's intention and biasing their perception even further toward the expected goal [see also Hudson et al (2016b)].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tomeo et al (2012) found that expert soccer players, compared to novices, more effectively predict the direction of a kick from another person’s body kinematics (see Aglioti et al, 2008; Mulligan et al, 2016, for similar results with basketball and dart players). Action prediction also affects perception (Springer et al, 2011) as predictions based on knowing another person’s task can bias how their subsequent actions are perceived (Hudson et al, 2016a,b). Due to the overlap of own and others’ sensorimotor representations, additional processes are needed to keep a distinction between self and other (Novembre et al, 2012; Sowden and Catmur, 2015) and to inhibit the tendency to automatically imitate another’s (incongruent) action (Ubaldi et al, 2015).…”
Section: Sharing Sensorimotor Informationmentioning
confidence: 99%
“…Participants watched hands reach for or withdraw from objects and judged the location of their sudden disappearance points. Even when the actions they saw were identical, participants perceived the hand's disappearance points closer to objects if they assumed a goal to pick them up, and further away when assuming a withdrawal (Hudson, Nicholson, Ellis & Bach, ; Hudson, Nicholson, Simpson, Ellis & Bach, ; for a similar effect in eye gaze perception, see Hudson & Jellema, ; Hudson, Liu, & Jellema, ).…”
Section: Evidence For Predictions When Observing Others' Actionsmentioning
confidence: 99%
“…Yet even though person knowledge may play a central role in predicting how others will behave, prior research on action observation has rarely addressed these contributions, focussing instead on the role of overt cues in action prediction (e.g., emotional expressions, Adams, Ambady, Macrae, & Kleck, ; Johnston, Miles, & Macrae, ; action kinematics, Bach et al, ; gaze, Pierno et al, ; explicit statements, Hudson, Nicholson, Ellis et al, ; Hudson, Nicholson, Simpson et al, ). Although these cues may indeed exert their effects by providing person information, such as implying others' goals or intentions, they could just as well be explained on the level of action alone, where certain cues (e.g., a smile) directly predict associated behaviours (approach), without drawing upon person information at all (e.g., Gergely & Csibra, ; Ruffman et al, ).…”
Section: Person Models As a Source And Target Of Predictionsmentioning
confidence: 99%